Portuguese library assessment practices and transitions: a meta-evaluation model for the Information and Knowledge Society - Pinto, Leonor Gaspar; Ochôa, Paula (Qualitative and Quantitative Methods in Libraries; Vol 4 No 3 (2015): September 2015 Issue, 2017)
The need for greater understanding of assessment practices and models highlights a deficit of an up-to-date meta-evaluation model, whilst articulating with new phases in Information and Knowledge Society (IKS) development. Current research carried out by each of the two authors led to a joint meta-evaluation study on the impact of main KIS transitions on performance evaluation models implemented in Portuguese libraries between 1970 and 2010. This paper aims to discuss the meta-evaluation model that was created in that context to explain the relations between IKS transitions and the development of library performance evaluation models. After an initial review of European IKS policies and strategies targeted at libraries and the exploration of the transition and meta-evaluation concepts, a brief characterization of the Portuguese Library System introduces the cycles of recognition, reinforcement, uncertainty and weakness of European IKS strategies that were identified in the Portuguese library scene. Using the CLPET Model, the main types of performance evaluation approaches used in Portuguese libraries are identified and categorized.  Based on the evidences gathered, the impacts of IKS transitions on library performance evaluation models in Portugal are then analysed and discussed.